The Ayyubid State in Egypt (567–648 AH): Its Emergence and Intellectual Civilization - سمران ضمياء موسى زيدان (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research aims to identify the Ayyubid state in Egypt (567-648 AH), its origins and intellectual civilization, considering that it had a great impact on the succession and development of Islamic civilization. This research is based on a descriptive and analytical study, by identifying the political conditions that paved the way for the Ayyubid state, shedding light on the origins of the Ayyubid state, and clarifying the factors of the prosperity of intellectual civilization in the Ayyubid era, then identifying the most famous scholars who came to Egypt in the Ayyubid era, and stating the intellectual and civilizational effects that led to the development of science in the Ayyubid era. One of the most prominent results that the research reached was that the Ayyubid state arose in Egypt, and extended to include the Levant, the Hijaz, Yemen, Nubia and some parts of the Maghreb. Saladin Yusuf bin Ayyub is considered the founder of the Ayyubid state. The Ayyubid era witnessed an unprecedented scientific and cultural renaissance, as scientific and intellectual life flourished due to several factors, most notably the encouragement and patronage of the caliphs and princes of the Ayyubid family for scholars. This contributed to the emergence of an elite of senior scholars and thinkers. In various fields of science, literature, and the arts, the efforts and significant contributions of scholars were evident in various fields of knowledge, whether in medicine, engineering, astronomy, jurisprudence and its principles, language and literature, or the flourishing of applied sciences